Government Accounting Policy Of Oil And Gas Revenue After Implementation Gross Split Contract: Quo Vadis? - Aprianto, Joko; Wibowo, Puji (Journal of Law, Administration, and Social Science, 2024)
Production Sharing Contract (PSC) is a popular scheme for managing interests between oil and gas companies as contractors and the central government as a principal. PSC has been becoming attractive for contractors because the contract provides an incentive, and cost-recovery scheme, whereas all production costs during exploration and exploitation stages would be recovered by the government. However, this long-standing contract creates serious problems regarding efficiency and government revenue aspects. To address these issues, in early 2017, the Ministry of Energy and Mineral Resources stipulate a new regulation to propose a new scheme contract namely gross-split. This policy aims to promote more investment in the oil and gas exploration sector so that lifting can be increased, and also, as an effort to eliminate the debate over cost recovery. In contrast to the cost recovery PSC, in a gross split PSC, there is no longer an assume and discharge facility for indirect taxes and other levies given to contractors. This study aims to determine the implications of the PSC gross split on the oil and gas revenue accounting policy. The author conducted interviews with several informants and analyzed the data using the interactive model of Miles and Huberman. As a result, the gross split implies the recognition of Oil and Gas revenue using gross principle